First, we plug the value of 2 for x.
This leads to 3(2)+y=a and 2(2)+5y=2a
or 6+y=a and 4+5y=2a
Rearranging, we have a-y=6 and 2a-5y=4
Multiplying the first expression by 5, we get 5a-5y=30 and 2a-5y=4.
3a=26 and a=26/3.
We can immediately multiply the first equation by 5, so we have the two equations:
15x + 5y = 5a
2x + 5y = 2a
Subtract the second from the first:
13x = 3a
Rearrange and divide by 3:
a = (13/3)*x
Substiute 2 for x:
a = (13/3)*2 or a = 26/3
(tertre added when he/she should have subtracted).